Integrated governance for managing multidimensional problems: Potentials, challenges, and arrangements - Haapasaari, Päivi; Ignatius, Suvi; Pihlajamäki, Mia; Bryhn, Andreas; Sarkki, Simo; Tuomisto, Jouni; Nevalainen, Lauri; Lehikoinen, Annukka; Assmuth, Timo; Romakkaniemi, Atso; Peltonen, Heikki; Kuikka, Sakari (Elsevier Science Ltd., 2021)
The implementation challenge of ecosystem-based (fisheries) management (EB(F)M) has entailed calls for integrated governance (IG) approaches in the marine field. We arranged an expert workshop to study the preconditions and applicability of IG, and to suggest how IG could be arranged in practice. Focusing on the management of the dioxin problem shared by the herring and salmon fisheries in the Baltic Sea, and using a coupled ‘insight network’- SWOT (strengths, weaknesses, opportunities, threats) methodology, we evaluated two scenarios: 1) IG of herring and salmon fisheries to benefit from collaboration between these fisheries that suffer from the same problem, and 2) IG between the fisheries sector and the food/public health sector to incorporate food safety in fisheries governance. Our results demonstrate that a variety of societal, political, institutional, operational, instrumental, and biological factors affect the applicability of IG in marine contexts, and work as preconditions for IG. While societal needs for IG were obvious in our case, as major challenges for it we identified the competing cross-sectoral objectives, path dependencies, and limitations of experts to think and work across fields. The study suggests that establishing an IG framework by adding new aspects upon the current governance structures may be easier to accept and adapt to, than creating new strategic or advisory bodies or other new capacities. Viewing IG as a framework for understanding cross-sectoral issues instead of one that requires a defined level and form of integrated assessment and management may be a way towards social learning, and thereby towards the implementation of more sophisticated, open and broad EB(F)M frameworks.
Keywords: Baltic herring; Baltic salmon; Ecosystem-based management; Food safety; Inter-sectoral collaboration; Knowledge co-creation; Multi-species management; Social-ecological problem; SWOT-analysis